2017
DOI: 10.4054/demres.2017.37.1
|View full text |Cite
|
Sign up to set email alerts
|

Fertility change in the American Indian and Alaska Native population, 1980–2010

Abstract: BACKGROUNDSince 1990, Vital Statistics reports show a dramatic decline in the total fertility rates (TFRs) of American Indian and Alaska Native (AI/AN) women in the United States. OBJECTIVEWe study whether the decrease in TFRs is due to a real change in fertility for a stable population; a compositional change in who identifies as AI/AN; or a methodological issue stemming from differences in identifying race across the data systems used to calculate fertility rates. METHODSWe use data from the decennial US Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Snipp (1997) shows that total fertility rates for Native American women are declining between 1970 and 1990 and that the total fertility rates for Native American women living in nonmetro areas are consistently higher than for those living in metro areas. Additionally, Cannon and Percheski (2017) find evidence that the declining total fertility rate for the American Indian and Alaska Native population is unlikely to be due solely to changes in self-identification in the census. They suggest changes in marriage patterns as one explanation for the changing fertility rates but recommend further investigation into geographic regions as a possible additional driver of these changing patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Snipp (1997) shows that total fertility rates for Native American women are declining between 1970 and 1990 and that the total fertility rates for Native American women living in nonmetro areas are consistently higher than for those living in metro areas. Additionally, Cannon and Percheski (2017) find evidence that the declining total fertility rate for the American Indian and Alaska Native population is unlikely to be due solely to changes in self-identification in the census. They suggest changes in marriage patterns as one explanation for the changing fertility rates but recommend further investigation into geographic regions as a possible additional driver of these changing patterns.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the lack of historical decennial census data makes it virtually impossible to use "cohort change ratios," a variant of the cohort-component method that is often employed in conjunction with decennial census data when a population is "small" and vital statistics data are not available (Baker, Swanson, Tayman, and Tedrow 2017). An example of the difficulty of this task is found in recent work by Cannon and Percheski (2017) who discuss some of the obstacles facing an analyst who attempts to assemble valid fertility rates for the American Indian and Alaska Native population from 1980 to 2010. As noted in the preceding section in regard to virtually all Native American tribes, in addition to changing self-identification in terms of race and ethnicity, these obstacles include under-registration in terms of vital event systems and ethnic/ race misclassification.…”
Section: Methodsmentioning
confidence: 99%
“…For the most recent period, a study by Amorevieta-Gentil et al (2013) for 1986 showed that trends in the total fertility rate (TFR) of the Registered Indian population followed trends for Canada as a whole, with about one child more on average and with no sign of convergence with the rest of the population during the period. Persistent higher fertility among Aboriginal people has also been observed in Australia and New Zealand (Johnstone 2011), while in the United States American Indians' and Alaska Natives' fertility has declined in recent years (Cannon and Percheski 2017).…”
Section: Introductionmentioning
confidence: 95%